2022
DOI: 10.1021/acsaem.2c02780
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a Buried Interface with Bulky Organic Cations for Highly Stable Flexible Perovskite Solar Cells

Abstract: Flexible perovskite solar cells triggered a vast interest within the scientific community, thanks to their broad commercialization prospects. However, the stability of these devices still poses one of the major concerns on the way to rapid industrial deployment. Here, we demonstrate an effective strategy to improve the technical aspects of this technology, improving the reliability and efficiency values of these devices. We apply large organic ammonium molecules for modifying a buried interface between a hole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…275 Although such PEAI-based cations are typically used to form low-dimensional perovskites, it has been found that the use of significantly lower concentrations to modify the two interfaces of IPSC would not alter the bulk perovskite crystal structure or its dimensions, but instead enhance them by facilitating both the formation of highquality perovskite films and by inducing effective defect passivation at the interface. 276 Also, nanopores at the perovskite/HTL interface are eliminated by modification near the bottom of the perovskite film. Therefore, it is expected that the simultaneous implementation of both modifications will lead to an increase in the relevant PV parameters of the cell, resulting in superior device performance.…”
Section: Multiple Interface Designmentioning
confidence: 99%
See 1 more Smart Citation
“…275 Although such PEAI-based cations are typically used to form low-dimensional perovskites, it has been found that the use of significantly lower concentrations to modify the two interfaces of IPSC would not alter the bulk perovskite crystal structure or its dimensions, but instead enhance them by facilitating both the formation of highquality perovskite films and by inducing effective defect passivation at the interface. 276 Also, nanopores at the perovskite/HTL interface are eliminated by modification near the bottom of the perovskite film. Therefore, it is expected that the simultaneous implementation of both modifications will lead to an increase in the relevant PV parameters of the cell, resulting in superior device performance.…”
Section: Multiple Interface Designmentioning
confidence: 99%
“…The device achieves an optimal PCE of 21.9% NiO x -based IPSC with multiple design guarantees for the interface . Although such PEAI-based cations are typically used to form low-dimensional perovskites, it has been found that the use of significantly lower concentrations to modify the two interfaces of IPSC would not alter the bulk perovskite crystal structure or its dimensions, but instead enhance them by facilitating both the formation of high-quality perovskite films and by inducing effective defect passivation at the interface . Also, nanopores at the perovskite/HTL interface are eliminated by modification near the bottom of the perovskite film.…”
Section: Multiple Interface Designmentioning
confidence: 99%